2005
DOI: 10.1073/pnas.0505901102
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin regulates serine phosphorylation and the cellular distribution of β-adducin through activation of protein kinase C

Abstract: Pleiotrophin (PTN) was found to regulate tyrosine phosphorylation of ␤-adducin through the PTN͞receptor protein tyrosine phosphatase (RPTP)␤͞ signaling pathway. We now demonstrate that PTN stimulates the phosphorylation of serines 713 and 726 in the myristoylated alanine-rich protein kinase (PK) C substrate domain of ␤-adducin through activation of either PKC ␣ or ␤. We also demonstrate that PTN stimulates translocation of phosphoserine 713 and 726 ␤-adducin either to nuclei, where it associates with nuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 45 publications
(40 reference statements)
0
60
0
2
Order By: Relevance
“…␤-adducin also was identified as a target of the PTN͞RPTP␤͞ -signaling pathway (3,4), and PTN disrupts ␤-adducin-actin-spectrin complexes supporting cystoskeletal stability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…␤-adducin also was identified as a target of the PTN͞RPTP␤͞ -signaling pathway (3,4), and PTN disrupts ␤-adducin-actin-spectrin complexes supporting cystoskeletal stability.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, because the malignant cells constitutively express Ptn, the malignant cells have a ''stable EMT'' or perhaps more appropriately, an ''arrested EMT.'' Pleiotrophin signals through inactivation of the endogenous protein tyrosine phosphatase activity of RPTP␤͞ ; it increases tyrosine phosphorylation of the different substrates of RPTP␤͞ through the persistent activity of tyrosine kinases acting at the same sites as RPTP␤͞ (2)(3)(4)(5). Pleiotrophin was the first natural ligand to be discovered for this class of receptor-type transmembrane tyrosine phosphatases (2) and the PTN͞RPTP␤͞ signaling pathway triggered by PTN is unique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these data were not reconciled with earlier studies that demonstrated that the Receptor Protein Tyrosine Phosphatase (RPTP) β/ζ is the functional receptor of PTN [15]; in those earlier studies, PTN was shown to inactivate RPTPβ/ζ and to increase tyrosine phosphorylation of the substrates of RPTPβ/ζ, which results from phosphorylation of these substrates by kinases that phosphorylate the same sites dephosphorylated by RPTPβ/ζ when cells are not stimulated by PTN. The levels of tyrosine phosphorylation of β-catenin [15] and of other substrates of RPTPβ/ζ, including β-adducin [16,17], Fyn [18], GIT1/Cat-1 [19], and P190RhoGAP [20], all are increased in PTNstimulated cells.…”
Section: Introductionmentioning
confidence: 97%